Transference costs and intersectoral mobility: explaining income differentials affecting the agricultural sector - Figueroa, Eugenio (Estudios de Economía, 2016)
The inhability of the agricultural sector to maintain the relative income level of the population devoted to the sector has been called the “farm problem” in the literature. The analytical wok on the farm problem” has been concentrated on the U.S. case. However, there is clear evidence that is also affects a broad set of LDC’s, in which high income differentials exist between agriculture and non-agricultural sectos. None of the various intented explanations for these return differentials has been fully satisfactory. Her, a new explanation is proposed, which emphasizes general equilibrium dynamic forces rather than partial equilibrium, thus giving insights into the short and long-run resource adjustment mechanisms. It is shown that high intersectoral transference costs of agricultural resources, are a key issue in understanding the farm problem. They explain not only the sluggish adjustment of factor return differentials, but also the persistence of factor return disparities across sectors even in the long-run.